Tingkat Kepuasan Kinerja IT Support di Divisi Marketing pada PT. Jalatama Artha Berjangka menggunakan Metode Service Quality - Mohamad Hilal Monoaarfa; Rouli Doharma (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
In this study, the researcher uses a quantitative research type, namely the researcher collects data on a certain population or sample. While the study was conducted in the marketing division at PT. Jalatama Artha Berjangka to analyze and calculate statistics using the service quality method. The results of this study are in the marketing division of PT Jalatama Artha Berjangka, I can draw the following conclusions: indicating that the satisfaction of IT Support performance in the Marketing Division at PT. Jalatama Artha Berjangka has not met expectations. Evaluation using the Service Quality method reveals a gap between expectations and performance provided by IT Support services and improvements and enhancements in IT Support services in the marketing division need to be prioritized to improve service quality and achieve a better level of satisfaction. Thus, this study provides an understanding of the condition of IT Support performance satisfaction in the Marketing Division of PT. Jalatama Artha Berjangka and highlights the importance of improvement efforts to increase user satisfaction with IT Support services.